The lived experiences of men who have sex with men when accessing HIV care services in Zimbabwe - Idah Moyo; Margaret Macherera; Azwihangwisi H. Mavhandu-Mudzusi (AOSIS, 2021)
Background: Key populations such as men who have sex with men are disproportionately affected by human immunodeficiency virus (HIV), yet they are underserved. This vulnerable group also faces stigma and discrimination when utilising the healthcare services. However, to achieve the HIV epidemic control, it is important for them to have access to HIV care services. Aim: The aim of this study was to explore and describe the experiences of men who have sex with men (MSM) as they accessed HIV care services in healthcare settings in Bulawayo, Zimbabwe. Setting: The study setting was healthcare facilities (state and private owned) in Bulawayo, Zimbabwe, that offer HIV care services. Methods: The study used a descriptive phenomenological design targeting self-identified MSM living with HIV. Data were gathered by using in-depth individual interviews that were audio recorded. Data saturation determined sample size. Data were transcribed verbatim and later analysed thematically. Results: The study revealed that counselling given to MSM was generalised and not individualised. Some clients faced stigma and discrimination after disclosure. Peer and family support were important in the journey to access HIV care services. Conclusion: An enabling environment was not provided for MSM clients to access HIV care services in the majority of health facilities. This calls for sensitisation and competency clinical training of service providers so that the diverse needs of MSM are met. Peer and family support for MSM needs to be strengthened.